Asthma: onset at young, persist when grow up - Siu, Ka Ka; Lin, Lok Yiu; Kwok, Wang Chun (Translational Pediatrics, 2026)
Asthma is a prevalent chronic respiratory disease that affects individuals across all age groups worldwide. It is characterized by airway inflammation, bronchial hyperresponsiveness, and variable airflow obstruction, which can lead to recurrent episodes of wheezing, breathlessness, chest tightness, and coughing. The age at which asthma first manifests play a crucial role in determining its underlying pathophysiology, clinical presentation, and management strategies. Broadly, asthma is classified into two categories based on age of onset: childhood-onset asthma and adult-onset asthma. Childhood-onset asthma typically begins during early childhood and often has a strong allergic component, whereas adult-onset asthma may develop later in life and can sometimes be associated with different triggers or comorbidities. These distinctions are important because they influence the disease’s clinical course, response to treatment, and long-term prognosis. Recognizing these differences allows for more targeted and effective management approaches tailored to each patient’s specific needs. This review aims to provide a comprehensive overview of childhood-onset asthma, including its underlying pathophysiology, diverse phenotypes, clinical features, diagnostic tools, and current treatment approaches. Special attention will be given to how childhood asthma evolves as patients grow older, including the transition from childhood to adulthood. Understanding these aspects is vital for optimizing management and improving outcomes for individuals affected by this chronic disease. By examining the unique features of childhood-onset asthma, healthcare providers can tailor interventions more effectively and anticipate potential challenges during the transition into adult care. Ultimately, a thorough knowledge of these differences can lead to better personalized treatment plans and improved quality of life for patients.